Malory's Originality A Critical Study of Le Morte Darthur - Lumiansky, R. M. (Johns Hopkins University Press, 2019)
Originally published in 1964. The book presents a commentary on Le Morte d'Arthur that illuminates Malory's literary aims and techniques. The author brings to bear several hitherto unused source materials on Malory's work and offers new analyses of his authorial purposes. Lumiansky argues that Malory wrote a single unified book rather than eight separate tales. The source of Malory's story is an Old French romance known as the Suite du Merlin. Lumiansky traces Malory's originality through Malory's treatment of the main generic features of the Suite du Merlin.